The Plundering of Jewish Property in Europe: Five Recent Publications Documenting Property Seizure and Restitution in Germany, Belgium, Norway, and Belarus - Dean, Martin (Holocaust and genocide studies, 2001)
Betrifft: “Aktion 3.” Deutsche verwerten jüdische Nachbarn. Dokumente zur Arisierung, Wolfgang DreBen, ed. (Berlin: Aufbau Verlag, 1998). Verfolgung und Verwaltung: Die wirtschaftliche Ausplünderung der Juden und die westfälischen Finanzbehörden, Alfons Kenkmann and Bernd-A. Rusinek, eds. (Münster: Oberfinanzdirektion Münster, 1999). Comptes d'une mort annoncée, Viviane Teitelbaum-Hirsch (Brussels: EditionLabor, 1997). The ReiseliBruland Report on the Confiscation of Jewish Property in Norway during World War II: Part of Official Norwegian Report 1997:22 (Oslo: ODIN [government publication], June 1997). “Nazi Gold” from Belarus: Documents and Materials, V. I. Adamushko, G. D. Knatko, et al., eds. (Minsk: National Archive of the Republic of Belarus, 1998).